1995
DOI: 10.1046/j.1365-313x.1995.08030451.x
|View full text |Cite
|
Sign up to set email alerts
|

Organ‐specific differences in the ratio of alternatively spliced chorismate synthase (LeCS2) transcripts in tomato

Abstract: The primary transcript of one of the two chorismate synthase genes (LeCS2) of tomato is differentially processed due to an alternative splicing of the third intron. A novel observation was made when the abundances of the two LeCS2-specific transcripts in different organs were analysed. The ratio of these two transcripts differs in RNA populations from different organs. Possible explanations for this finding and its potential physiological impact for plant metabolism are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…Results of the few functional analyses that have been conducted indicate roles for AS in plant processes such as some metabolic pathways (Gorlach et al 1995), catabolic pathways (Kopriva et al 1995), and mRNA processing (Kalyna et al 2006), and AS impacts many important plant process such as photosynthesis, defense response, flowering, and cereal grain quality (Reddy 2007).…”
Section: Functional Ontology Of As Genesmentioning
confidence: 99%
“…Results of the few functional analyses that have been conducted indicate roles for AS in plant processes such as some metabolic pathways (Gorlach et al 1995), catabolic pathways (Kopriva et al 1995), and mRNA processing (Kalyna et al 2006), and AS impacts many important plant process such as photosynthesis, defense response, flowering, and cereal grain quality (Reddy 2007).…”
Section: Functional Ontology Of As Genesmentioning
confidence: 99%
“…Subsequent characterization of plant genes that are alternatively spliced included RNA polymerase II (Dietrich et al 1990), chorismate synthase (Gorlach et al 1995), H protein (Kopriva et al (Fu et al 2005) was used for maize AS analysis, Transcript isoform determination for all three plant species was carried out with the PASA spliced alignment software described by Haas et al (2003). The data for human AS event types was reported by Kim et al (2007) 1995), Arabidopsis U1 snRNP 70K (Golovkin and Reddy 1996), the maize regulatory MuDR transposable element (Hershberger et al 1995), the maize loci for glutathione S-transferase (bronze2) (Marrs and Walbot 1997), and wx (Marillonnet and Wessler 1997).…”
Section: Alternative Splicing In Plantsmentioning
confidence: 99%
“…Interestingly, two genes (one SK gene, At2g21940, and one EPSPS gene, At1g48860) that were not induced by wounding were found to be upregulated in AtMYB15-ox plants ( Figure 4C). It has been reported that ozone and pathogen elicitors are able to trigger extensive activation of shikimate pathway genes and many genes encoding enzymes of the shikimate pathway show tissue-specific expression patterns (Gasser et al 1988;Henstrand et al 1992;Gorlach et al 1995a;Janzik et al 2005;Kasai et al 2005). The fact that AtMYB15 overexpression was able to activate these two genes that were not wound inducible may also reflect the sophisticated action of AtMYB15 over different tissue types or in response to different stimuli.…”
Section: Atmyb15mentioning
confidence: 99%
“…However, in plants, the products of the shikimate pathway have dual functions not only as building blocks of protein synthesis, but also as the precursors of a variety of secondary metabolites, such as lignins (Ehlting et al 2005), indolic acetic acid (Ljung et al 2002), alkaloids (van der Fits and Memelink 2000), and phytoalexins (Kuc and Rush 1985). These compounds, the biosynthesis of which is regulated developmentally and environmentally (Gasser et al 1988;Keith et al 1991;Gorlach et al 1995aGorlach et al , 1995b, play important roles in growth control, physical support, electron transport, and defense responses.Plants respond to wounding by increasing the production of compounds involved in the healing of wound damage and defense against microbial invasion. It has been reported that,…”
mentioning
confidence: 99%